Morphological Identification of Five Endophytic Fungus Isolates from Shallots and Their Ability to Inhibit Alternaria porri Ellis Cif - Yetti Elfina; Muhammad Ali; Siti Fatimah Wulandari; Roy Ibrahim (Universitas Pattimura, 2022)
One of the obstacles in shallot cultivation is the attack of purple spot disease caused by the fungus Alternaria porri. Alternative disease control that can be done and is relatively safe for the environment is biological control using indigenous endophytic fungi isolated from the plant to control the disease. Biological control using indigenous microorganisms will be more successful because of their higher compatibility and adaptability. This study aimed to characterize and determine the ability of 5 isolates of endophytic fungi islated fron shallot to control the pathogenic fungus Alternaria porri in vitro. It was carried out through observation and experiment, consisting of: (1) isolation and characterization of endophytic fungi on shallots and (2) in vitro testing of endophytic fungi against A. porri. The data obtained from observations were analyzed descriptively and the data from the inhibitory test were analyzed by analysis of variance, to test five endophytic isolates obtained from shallot root and leaf tissues. The results of this study indicated that: (1) isolate B belonged to the genus Nigrospora, isolate C to the genus Aspergillus, isolate D to the the genus Epicoccum, whereas isolates A and E were unknown; (2) 5 isolates of this indigenous endophytic fungus were hypovirulent with a disease severity index <2 so that they could be used as disease control agents; (3) 5 isolates of indigenous endophytic fungi of shallots showed inhibition ranging from 47.76%-55.25%, with isolate C genus Aspergillus having the highest inhibition with a percentage of 55.25%.